Ta grade 3/high grade non-invasive bladder cancer: Should we perform a second TUR? - BEKİROĞLU, GÜLNAZ NURAL (WILEY, 2021)
Purpose To evaluate the effect of second transurethral resection (TUR) on oncological outcomes, according to the presence or absence of detrusor muscle in the initial TUR of patients with pTa Grade 3/high grade (G3/HG) tumours, who received at least 1 year of maintenance Bacillus Calmette-Guerin (BCG) therapy. Patients and methods In this retrospective study, we evaluated the effect of second TUR on oncological outcomes of 93 patients with pTa G3/HG tumours, according to the presence or absence of muscle in the initial TUR. All patients received maintenance BCG therapy according to the SWOG protocol. Results Median follow-up was 36 months. If muscle is present in the initial TUR, a second TUR significantly increased median time to first recurrence, compared to those without a second TUR (77.6 vs 36.9 mos, P = .0086). If muscle is missing in the initial TUR, a second TUR significantly decreased recurrence rate (20% vs 66.7%, P = .002), increased median time to first recurrence (78.9 vs 42.7 mos, P = .0001) and median time to progression (22 vs 7 mos, P = .05), compared to those without a second TUR. Conclusion In patients with pTa G3/HG tumours, if the muscle is missing in the initial TUR, a second TUR should be performed in order to attain lower recurrence rates and longer median time to recurrence and progression. If the muscle is present in the initial TUR, a second TUR will only increase median time to first recurrence.
Keywords: TRANSURETHRAL RESECTION